Altered States: Liminality and Consciousness During COVID. (2nd February 2022) - Torres, Nicole
Abstract: This editorial discusses the function of COVID as what the Indigenous scholar and psychologist, Eduardo Duran, describes as a "great teacher." The author engages with the opportunities of learning that the COVID‐19 pandemic has provided, especially in the realm of anthropological studies of consciousness. The author encourages both scholars and practitioners to use the current pandemic as an opportunity to practice what Andy Fisher identifies as a "decolonial praxis, " as a tool for liberation and healing.